A Follow Up Study on Lung Cancer Survival in the State Hospital in East Coast State of Pahang - Balakrishnan, Sivasubramaniam; Ab. Rahman, Jamalludin; Koya Kutty, Shaheedah; Megat Razeem Abdul Razak,; Aishah Ibrahim,; Soon Hin, How (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: There is lack of data of lung cancer survival in Malaysia. MATERIAL AND METHODS: This study was to determine the survival of lung cancer patients and factors affecting the survival in Kuantan, Pahang. A total of 170 lung cancer patients confirmed by histology from 1st January 2014 to 31 December 2017 were recruited in the study. Their demographic data, ECOG performance status, staging and treatment were recorded. Survival time was defined in weeks from the date of histological diagnosis made to the date of death of the patients. Kaplan-Meier curve was used to determine the median overall survival and log-rank test was used to test the survival differences between each subgroup. Multivariate analysis using COX regression was used to determine factors affecting its survival. RESULTS: The median age of the 170 patients was 63 years old, majority were males (74%) and smokers (64%). Adenocarcinoma (74.7%) was the most common histology followed by squamous cell carcinoma (18.8%). Almost all patient presented at the clinic at stage 3 or 4 (98%) but majority had ECOG 0-2 (64.3%). Median overall survival was 28.7 weeks. In the multivariate analysis, “supportive treatment” and “poor ECOG performance status” were independent predictors of death with the hazard ratio of 1.4 (95%CI 1.17 to 1.66) and 3.0 (95%CI 2.05 to 4.39) times respectively. CONCLUSION: Majority of lung cancer patients in Pahang presented with advanced disease with overall median survival of 28.7 weeks. Patients treated with supportive care and poor ECOG performance status were the two independent poor prognostic factors for survival.